Studi Komparasi Analisis Muatan Nilai-nilai Pancasila Pada Buku Siswa Tema Kepemimpinan Kelas VI - Elly Masyitoh; Diah Sunarsih; Moh. Toharudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was motivated by students who did not know the distribution of Pancasila values contained in student books. This study aims to 1) find out the values of Pancasila contained in student books published by the Ministry of Education and Culture, 2) find out the values of Pancasila contained in student books published by Zamrud and 3) to find out the similarities and differences in Pancasila values in student books published by the Ministry of Education and Culture. Culture with Emeralds. Data collection techniques using documentary studies. Data analysis used is data collection, sample determination, recording, reduction, drawing conclusions and analysis. The results showed that 1) the values of Pancasila contained in student textbooks published by the Ministry of Education and Culture were 95 findings; 2) The value of Pancasila contained in student textbooks published by Zamrud is 75 findings; 3) the similarities between the two textbooks are that the student textbooks used in the learning of the publishers of the Ministry of Education and Culture and Emeralds contain all the values of Pancasila, these values consist of the values of divinity, humanity, unity, democracy and justice. The difference between the two textbooks is that the Pancasila Values spread in the book are not balanced, so that the Ministry of Education and Culture's book has a higher content of Pancasila Value than the book from Zamrud.